(untitled) (The Journal of Medicine, Humanity and Media, 2025)
This study investigates Chinese young adults’ perceived credibility of parent-shared online health information, their intention to adopt such information, and the potential influencing factors. Based on a sample of 356 survey responses, t-tests and hierarchical regression analyses were conducted. Results show that, compared to health information shared by parents, young adults in mainland China generally place greater trust in health information they have obtained themselves. Moreover, both intergenerational intimacy and eHealth literacy were positively associated with perceived message credibility. Building on the regression results, structural equation modeling (SEM) was employed as an exploratory analysis to examine the potential mediating role of perceived message credibility. The SEM results indicated that perceived message credibility partially mediated the relationship between intergenerational intimacy and information adoption intention, whereas it fully mediated the effect of eHealth literacy on adoption intention. By extending its applictaion to the context of health communication across generations in Chinses family, this study enriches the literature on message credibility, and provides possible ideas on how to improve intergenerational health communication.